1995
DOI: 10.1007/bf00191570
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of labdenediol and sclareol in cell-free extracts from trichomes of Nicotiana glutinosa

Abstract: Biosynthesis of the diterpenes labdenediol andsclareol from all trans-geranylgeranyl pyrophosphate was observed in cell-free extracts prepared from leaf midvein epidermal peels of Nicotiana glutinosa 24A. The bioactivities were shown to be exclusively localized in trichomes, to be conferred by a soluble enzyme(s), and to resemble other plant terpene cyclase activities in basic characteristics. Chromatographic methods for protein purification including gel filtration, anion exchange, hydroxyapatite chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 16 publications
(24 reference statements)
3
36
0
2
Order By: Relevance
“…Solanaceae trichomes are also known to express terpene synthases and produce a variety of terpenes (Guo and Wagner, 1995). In tobacco, the diterpenes cembratrieneols (CBTols) and cembratrienediols (CBTdiols), important defense compounds, are produced in the trichomes (Wang and Wagner, 2003;Wang et al, 2001).…”
Section: Terpenesmentioning
confidence: 99%
“…Solanaceae trichomes are also known to express terpene synthases and produce a variety of terpenes (Guo and Wagner, 1995). In tobacco, the diterpenes cembratrieneols (CBTols) and cembratrienediols (CBTdiols), important defense compounds, are produced in the trichomes (Wang and Wagner, 2003;Wang et al, 2001).…”
Section: Terpenesmentioning
confidence: 99%
“…Biosynthesis of secondary metabolites, including monoterpenes (Turner et al, 1999), sesquiterpenes (Crock et al, 1997), and diterpenes (Guo and Wagner, 1995), occurs in the secretory head cells of the leaf glandular trichomes. Ultrastructural analysis of tobacco short (unicellular stalk and pluricellular head) and long (multicellular stalk and uni/pluricellular head) glandular trichomes showed that both have secretory properties (Akers et al, 1978).…”
Section: Nppdr1 Expression In N Plumbaginifoliamentioning
confidence: 99%
“…Sclareol belongs to the terpenoid group of secondary metabolites, a large class of molecules involved in various physiological processes, including plant-pathogen (Kennedy et al, 1992) and plant-insect (De Moraes et al, 2001) interactions. Sclareol, which also inhibits the growth of certain pathogenic fungi (Bailey et al, 1975), is synthesized in tobacco leaf trichomes (Guo and Wagner, 1995) and is, like some other diterpenes, a major constituent of the exudate covering the leaf surface (Colledge and Reid, 1975).…”
mentioning
confidence: 99%
“…In addition to balsam fir, a gymnosperm tree, only a few angiosperm plant sources, such as tobacco (Nicotiana tabacum; family Solanaceae) trichomes (8,9) or the tuberous roots of Bolivian sunroot (Polymnia sonchifolia; family Asteraceae) (10) are known to produce cis-abienol 4 in amounts that are relevant for industrial scale extraction. The importance of cisabienol 4 as a plant-derived precursor for the fragrance and bioproducts industry has spawned an interest in the discovery of the relevant biosynthetic genes and enzymes and their future application in metabolically engineered microbial or plant production systems.…”
mentioning
confidence: 99%